The Effect of Tai Chi Intervention on Sensory Function in the Elderly Improvement Effect Based on Skin Sensitivity and Proprioception - He, Qinxuan; Liu, Ziyin (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details